From West Country Farmers to W. H. Ireland, the Shakespeare Forger: The Previous Owners of Thomas Tusser's Five Hundreth Pointes of Good Husbandrie (1599), BL, C.122.bb.40. (2019) - Smith, Maddy
No abstract available